PSX-A-10 Late-Breaking: Effects of paternal high energy diets on blastocyst development during in vitro embryo production in the bovine. (8th October 2021) - Davis, Dylan B; Seekford, Zachary; Dickson, Mackenzie; Gonçalves, Lucas; Burato, Samir; Holton, Matthew P; Gordon, Julie; Pohler, Ky G; Bromfield, John; Lamb, G Cliff C; Pringle, Dean; Stewart, R Lawton; et al.
Abstract: The objective of this study was to evaluate the effect of paternal high energy diets on blastocyst development during in vitro embryo production (IVP). Eight sires were stratified by body weight (initial BW = 946 ± 85 kg) and randomly assigned to the same diet (NEm = 2.10, NEg = 1.44, CP = 14.1%, NDF = 16.6%, DM basis) fed at two different inclusion rates while having ad libitum access to bermudagrass hay (NEm = 1.02, NEg = 0.45, CP = 10.2%, NDF = 71.6). After a 10-d adaptation period, sires were individually fed to receive 0.5% (MAINT) or 1.25% [High gain (HG)] of their BW daily for 67 days. At the end of the feeding period, semen was collected through electroejaculation and frozen. Antral follicles were aspirated from ovaries obtained from a slaughterhouse and utilized for IVP in 4 independent replicates (n = 2, 227 total oocytes). Cleavage rates were evaluated 48 h after fertilization and blastocyst development rates were evaluated after 7 days of embryo culture. The proposed treatments successfully induced differences in BW gain (P < 0.01; 2.28 vs -0.04 kg/d) and carcass composition (Rump fat: 1.63 vs. 0.41 cm, P = 0.08; Rib fat: 1.06 vs. 0.41 cm, P = 0.02; intramuscular fat: 3.5 vs. 3.0%, P = 0.36; for HG vs. MAINT sires, respectively). There was a significant decrease in cleavage rates (69.9 ± 2.5 vs. 65.0 ± 2.7; P < 0.04), blastocyst rate as a percentage of oocytes (16.7 ± 2.9 vs. 11.5 ± 2.1; P < 0.01), and blastocyst rates as a percentage of cleaved structures (24.1 ± 3.8 vs. 11.5 ± 2.1; P < 0.01) for HG compared with MAINT sires. In conclusion, sires fed diets that induce highly anabolic conditions had impaired blastocyst development compared to sires fed a maintenance diet.